The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ijc.25030
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycan based models improve diagnostic efficacies in hepatitis B virus‐related hepatocellular carcinoma

Abstract: The early diagnosis of hepatocellular carcinoma (HCC) is of great clinical desirable due to lack of specific and sensitive markers. Alterations in the sugar chains of glycoprotein synthesized by the liver contribute to the molecular basis of abnormalities in carcinogenesis. This study aims to construct and assess the diagnostic value of N-glycan based diagnostic model in HCC identification and follow-up. A total of 393 subjects including HBV-related HCC, liver fibrosis and healthy controls were recruited. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 41 publications
1
44
1
Order By: Relevance
“…It's worth noting that in our study the fuc-fetuin A concentration could not distinguish HCC from LC, which is not consistent with our previous reports in which the total specific fucosylated N-glycan in serum was used to differentiate HCC and LC [3,17]. We attributed this to the different type of main fucosylation for fetuin A in HCC and LC, because the AAL lectin used in the present study bind both core and out arm fucosylated glycan.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…It's worth noting that in our study the fuc-fetuin A concentration could not distinguish HCC from LC, which is not consistent with our previous reports in which the total specific fucosylated N-glycan in serum was used to differentiate HCC and LC [3,17]. We attributed this to the different type of main fucosylation for fetuin A in HCC and LC, because the AAL lectin used in the present study bind both core and out arm fucosylated glycan.…”
Section: Discussioncontrasting
confidence: 76%
“…Many reports have revealed that increases in the levels of fucosylation of serum glycoproteins occur with the development of HCC [13][14][15][16]. Previous studies from our group also validated these variances between the sera of HBV-related HCC patients and fibrosis or cirrhosis patients in Chinese population [3,17]. As for fetuin A, it has also been reported that its concentration in serum decreased in both LC and HCC [11], while the fucosylated level of fetuin A elevated in HCC [5,16].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…DSA-FACE is a simple and efficient technology for measuring N-glycan changes in serum. We previously used the technology to assist in the diagnosis of HCC, CRC, and gastric cancer [29][30][31]. The study was designed to target analysis of the aberrant N-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Total serum glycoproteins, serum IgG, IgG-L3, and IgG-L3 lacking core-fucose were analyzed for N-glycan structure with DSA-FACE as described previously. 33,34 The results were analyzed using the GeneMapper v3.7 software (Life Technologies Corporation).…”
Section: Tissue Array Construction Immunohistochemistry and Immunofmentioning
confidence: 99%